Graphene Oxide: Purified Graphene Oxide Dispersions Lack In Vitro Cytotoxicity and In Vivo Pathogenicity (Adv. Healthcare Mater. 3/2013). Issue 3 (6th March 2013) - Ali‐Boucetta, Hanene; Bitounis, Dimitrios; Raveendran‐Nair, Rahul; Servant, Ania; Van den Bossche, Jeroen; Kostarelos, Kostas
<x xml:space="preserve">Abstract</x> Preparation of a high dispersibility graphene oxide (GO) that can be reliably used in biological investigations is reported by Kostas Kostarelos and co‐workers on page 433. Exposure of cells and tissue to the graphene oxide indicated a lack of cytotoxic responses in human cell cultures (in vitro) and after injection to living animals (in vivo). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>